PERTIMBANGAN HAKIM TERHADAP KETERANGAN AHLI PADA TINDAK PIDANA KORUPSI PENGADAAN BARANG/JASA PEMERINTAH (Analisis Putusan Nomor : 2421k/Pid.Sus/2016 Dan Putusan Nomor : 32/Pid.Sus-Tpk/2016/Pn.Pdg) - Satria Putra, Agung (Universitas Ekasakti, 2022)
The judge's consideration of the expert's statement from the LKPP RI on corruption in the Government Procurement of Goods/Services was used as the basis for making a decision in the form of punishment, which in Decision Number: 2421 K/PID.SUS/2016/PN/PDG the defendant as the Budget User has committed mistakes in classifying procurement packages that should be done separately but combined, determine the winner of the tender before the tender process is carried out. In the Decision Number: 32/Pid.Sus-TPK/2016/PN.Pdg in the opinion of the Expert it is a violation when the work is not completed, then the implementation guarantee cannot be realized/disbursed in accordance with what is stipulated in Article 3 Paragraph (1) letter f and Paragraph (2) letters b, e, f, g and h of Perka LKPP Number 7 of 2011 concerning Technical Guidelines for Black List Operations. This LKPP Expert's consideration is used as the basis by the Judge in his decision. The application of the punishment in Decision Number: 2421K/PID.SUS/2016 is to declare the defendant guilty for fulfilling the elements of Article 3 of the Corruption Crime Act. Sentenced to a sentence of 2 years 6 months in prison, and a fine of Rp. 50,000,000. The Decision Number: 32/Pid.Sus-TPK/2016/PN.Pdg states that the defendant is proven guilty of abusing his authority on the joint procurement of government goods and services as regulated in Article 3 of the Anti-Corruption Law and is sentenced to imprisonment for 1 (one) year. ) years and a fine of Rp. 50,000,000.00 (fifty million rupiahs) provided that if the fine is not paid, it will be replaced with imprisonment for 1 (one) month. This penalty is lighter than the decision in Decision Number: 2421K/PID.SUS/2016 due to the consideration of the defendant's ignorance of several provisions for the procurement of government goods and services.